A pilot study on a proposed discusion-based information literacy program in the Quezon City Public Library - Krus na Ligas Branch - Valebia, Joanne A.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
With the obvious inadequacy of the public school system in the Philippines, it is apparent that information illiteracy is becoming a threat to future generations. Inadequate structures, facilities, and manpower for the education sector results in the poor development of the future leaders of this country. It is in this light that the study focused on the untapped potential of library and information professionals to supplement and complement the rising need for instruction that leads to the development of information literate independent learners.
Through the development and implementation of a proposed information literacy program, the study was able to reach out to 10 students from the Quezon City Public Library in Krus na Ligas who actively participated in an experiment-like setting. These students were later bracketed into control and experimental groups. Assessment tools derived from the information literacy resources provided by the American Association of School Librarians and the Association for Educational Communications and Technology and adapted to the needs of the local public library readers were used to monitor and evaluate the progress of the program's young participants.
The data gathered and analyzed from the observations and the assessment tools revealed that 5 out of 5 participants from the experimental group exhibited more than 50% undeniable and observable improvement individually throughout the program as opposed to the arbitrary improvements (0% to 49%) of the individual members of the control group.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Quezon City Public Library - Krus na Ligas Branch; Information literacy -- Philippines